THE RELEVANCE OF PEACE EDUCATION IN NURTU RING A CULTURE OF PEACE - Obe, Olubunmi Oyewusi; Fukpene, Baitei (FPIPSKR Universitas PGRI Semarang, 2026)
ABSTRACTPeace does not come with our deoxyribonucleic acid (DNA). To get peace, we need to teach peace. Since the end of the Second World War in 1945, rigorous approaches to the study of peace emerged across the globe. Hence, institutions of higher learning around the globe began to develop keen interest in the question of peace. It is in this regard that peace is being researched and taught as peace and Conflict Resolution in a growing number of tertiary institutions and locations. Despite the countless scholarly articles on peace in Nigeria's tertiary institutions of learning for several decades, the question that keeps lingering among scholars is the perceived disconnect between the theories of Peace and Conflict Resolution as taught in the tertiary institutions and the security challenges Nigeria is facing. It is evident that Nigeria still remains one of the conflict ridden areas around the globe. As such, this article examines the relevance of peace education. In examining this, the article focuses on the what peace is all about, strategies of achieving peace, peace education, the scope of peace education, Objectives of peace education, the difference between peace education and education for peace, importance of peace education, ethical policies and practices in school environment for peace education. Finally, the article will be concluded with developing peace education curriculum. Historical method will be used in collection, collation and analysis of data.